Autoestima e ensino de inglês: uma proposta didática para o contexto público - Silva, Lucas Rafael da (Universidade Federal de São Carlos, 2020)
The self-knowledge and self-value are important factors in the development of a healthy identity. That is why the self esteem - seen as a process of building your own image according to the outside world - is an important theme in Brazilian public high school classes. The aim of this research is to make a theorical reflection of an instructional material developed to the self esteem theme in English classes, showing that official documents foresee the development of the affection and the impact of the self esteem in the teaching and learning process of a language. In a bibliographic research, based on the critical linguistic education thoughts, this study ends with some reflections about a instructional material with the self esteem theme, its importance in the teaching process and also about the teacher’s role in a critical teaching.
Self-esteem and English teaching: a pedagogical proposal for the public context
Keywords: Ensino de inglês; Educação linguística crítica; Autoestima; English language teaching; Critical language education; Self esteem; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA